2021
DOI: 10.21608/mjvh.2021.211713
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatocellular carcinoma in Mansoura university Hospitals: A case-control study of risk factors.

Abstract: Background and aims.Hepatocellular carcinoma (HCC) is the most common primary liver cancer and is one of the leading causes of cancer related deaths. The aim of this study is to investigate characters and risk factors in the development of hepatocellular carcinoma (HCC) in Mansoura University Hospitals. Methods.The study included 220 patients with HCC plus 246 control patients from general population of rural areas of Dakahlia. All the study population was randomly selected. Diagnosis of HCC was based on ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In this study, bilharzia antibodies were present in 61.9% of the 21 HCC patients. Our findings concur with those of Ramadan et al (2021), who found that 67.7% of Egyptian HCC patients had schistosoma antibodies. Bilharzia was reported in this analysis as a risk factor for HCC (OR=1.625, 95% CI 0.558-4.73).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, bilharzia antibodies were present in 61.9% of the 21 HCC patients. Our findings concur with those of Ramadan et al (2021), who found that 67.7% of Egyptian HCC patients had schistosoma antibodies. Bilharzia was reported in this analysis as a risk factor for HCC (OR=1.625, 95% CI 0.558-4.73).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, 86.8% of the HCC group was males, which is consistent with the findings of Ramadan and his colleagues, who demonstrated the predominance of HCC in males. In addition, they illustrated that variations in the level of exposure to risk factors could explain the importance of other genetic factors linked to other X-linked genetic factors and sex hormones [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis and fluorescence detection were conducted using 7500 ABIPRISM v.2.0.1 (Applied Biosystems, USA). The relative quantification (RQ) of the gene expression was assessed through the utilization of the comparative 2-ΔΔCT technique [ 12 ].…”
Section: Methodsmentioning
confidence: 99%